2017
DOI: 10.1111/1346-8138.13792
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble interleukin‐2 receptor level is more sensitive than angiotensin‐converting enzyme or lysozyme for diagnosis of sarcoidosis and may be a marker of multiple organ involvement

Abstract: Skin lesions in sarcoidosis are often the initial symptoms that enable the dermatologist to be the first to diagnose this granulomatosis. However, diagnosis is sometimes very problematic. In 2015, the diagnostic criteria for sarcoidosis were updated in Japan, with elevated serum soluble interleukin-2 receptor (sIL-2R) replacing negative tuberculin reaction. Therefore, we assessed the clinical utility of sIL-2R compared with two other common markers, angiotensin-converting enzyme (ACE) and lysozyme, in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 33 publications
4
44
0
1
Order By: Relevance
“…In sarcoidosis, increased level of sIL‐2R in serum and bronchoalveolar lavage fluid (BALF) has been reported, and serum level of sIL‐2R was correlated with various indices of its disease severity, including ACE, radiographic stage of disease, 67 Ga scintigraphy uptake and CD4 + T lymphocyte number in BALF . We previously reported that sIL‐2R could be considered as a good marker in support of diagnosis and a potential indicator of disease activity . Interestingly, SSc patients were also reported to have high sIL‐2R levels in circulation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In sarcoidosis, increased level of sIL‐2R in serum and bronchoalveolar lavage fluid (BALF) has been reported, and serum level of sIL‐2R was correlated with various indices of its disease severity, including ACE, radiographic stage of disease, 67 Ga scintigraphy uptake and CD4 + T lymphocyte number in BALF . We previously reported that sIL‐2R could be considered as a good marker in support of diagnosis and a potential indicator of disease activity . Interestingly, SSc patients were also reported to have high sIL‐2R levels in circulation .…”
Section: Discussionmentioning
confidence: 99%
“…The cut‐off value for CLEIA by using STACIA MEBLux test Scl‐70 or STACIA MEBLux test RNP was less than 10.0 U/mL for both. Complete medical histories, clinical examinations and laboratory tests were conducted for all patients at the first visit, as described previously . Skin lesions were assessed by biopsy; chest radiogram and high‐resolution computed tomography were used to assess pulmonary involvement, including bilateral hilar lymphadenopathy (BHL), parenchymal infiltrates or pulmonary fibrosis; and eye involvement, including uveitis, was evaluated by split‐lamp and funduscopic examination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, sIL-2R level has been reported to be a better marker for the diagnosis of sarcoidosis and the assessment of sarcoidosis activity than ACE and lysozyme. 17 Gallium-67 scintigraphy is used to identify the inflammatory areas and as an adjunctive tool in the diagnosis of sarcoidosis. 18 It is also useful for monitoring the effectiveness of steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of angiotensin converting enzyme are often absent in Löfgren syndrome 5. Studies show that an elevated level of soluble IL-2 receptor is a more sensitive marker for diagnosis of sarcoidosis, and is an indicator of disease activity,9 but testing is not widely available. Chest radiography is often requested to look for hilar lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%